Evaluation of Chubak aqueous extract in parasite decontamination on vegetables and comparison with commercial detergent in Sari - M Azadbakht; H Ziaee; Z Yousefi; B Shabankhani; AA Mehralian (Institue of Medicinal Plants, ACECR, 2005)
Objectives: Use of surfactants and chemicals for washing and parasite decontamination from vegetables is not recommend-ed by W.H.O. due to itchr('39')s penetration in vegetables parenchyma and probable cause of improper taste and odor and toxicity. Some surveys showed "soap-roots" rhizomes (Chubak) to contain Saponin like constituents. Those are effective on surface tension reduction and so are prefered to chemical washers. This research was designed to study plant effect on Parasite removal from vegetables and itchr('39')s comparison with disinfectant and commercial detergent in Sari City (Mazandaran Province-north of Iran). Material and methods: "Soap-roots" aqueous extract (1, 5, 10, 15, and 20 percent) was prepared from the Acanthophyllum squarrosum (Caryophyllaceae) rhizome by maceration method. 100 g of parsley vegetable samples was taken randomly from shopping centers. The samples were placed in contact with "Soap-roots" aqueous extract for zero and 15 minutes according to the W.H.O. guidelines. Then the effluent was centrifuged and evaluated for parasite decontamination as qualitatively and quantitatively by Mc-master counting slide (0.3 mm). In addition in this research parasite decontamination by commercial detergent (10%) was performed with contact times 0 and 15 minutes and also pure water as blank. Results: Maximum parasite decontamination by "Soap-roots" aqueous extract and commercial detergent (10%) at 0 minute contact time obtained was 84 and 97 parasite eggs (parasite), respectively. Also maximum parasite decontamination by "Soap-roots" aqueous extract and commercial detergent (10%) and blank water at 15 minutes contact time obtained was 230, 26 and 64 parasite ova (parasite), respectively. In this research the best parasite decontamination range by "Soap-roots" aqueous extract was obtained at concentrations of 10 to 20 % and contact time of 15 minutes. Quantitavely, maximum parasite ova (parasite) decontamination from vegetable samples by "Soap-roots" aqueous extract (10%) and 15 minutes contact time released 230 parasites. This numbers included 22 alive and active nematode larva, 197 alive larvas and 20 Parameciumia.